Exploring the Nexus of Feeding and Processing: Implications for Meat Quality and Sensory Perception - Sandra S. Q. Rodrigues; Ana Leite; Lia Vasconcelos; Alfredo Teixeira (Foods)
The intrinsic quality of meat is directly related to muscle and fat tissues. Factors such as the rate and extent of anaerobic glycolysis affect muscle pH, influencing the meat’s color, water holding, and texture. Postmortem anomalies can result in deviations from this intrinsic quality. The animals’ diet plays a crucial role in meat quality. Specific nutrients, such as proteins, vitamins, and minerals, affect meat’s texture, flavor, and juiciness. Feeds rich in omega-3 fatty acids can improve the sensorial quality of meat. Meat processing and methods such as aging, marinating, and cooking affect the texture, flavor, and juiciness, which can be evaluated by specific equipment or trained or untrained consumers. This comprehensive review investigates the relationship between animal feeding practices and meat processing techniques and their combined impact on meat quality and sensory perception. By synthesizing recent research, we explore how various feeding protocols (including diet composition and feed additives) and processing methods shape meat products’ nutritional value, texture, flavor profile, and overall consumer appeal. Understanding this nexus is crucial for optimizing meat quality while ensuring sustainability and safety in the food supply chain.